Uncommon Word Order of Yoda in Star Wars Movie Series: A Syntactic Analysis (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This paper analyzes Yoda's syntax order to discover the word order which occurs in his speeches and the factors affecting his preferred syntax. Data were collected from Yoda's utterances in George Lucas' Star Wars saga. Yoda, who speaks English, expresses his thoughts in an unusual structure which might not be recognized by the existing rules of syntax. Instead of speaking in the traditional Subject-Verb-Object syntax, Yoda speaks in Object-Subject-Verb and Verb-Object-Subject syntax. This study employs content analysis, diving into seven Star Wars movies from the Saga. Out of 169 sentences Yoda uttered, the researchers discovered three factors affecting his preference to use the unusual syntax, namely Yoda's origin, personality and traits, and power and abilities.